Invisible Itches: Insect and Non-Insect Causes - M.F. Potter; P.G. Koehler (EDIS)
This document explores the various causes of itching and irritation, emphasizing that not all are due to insect bites. It identifies four main sources: obscure biting arthropods, personal-use products, environmental factors, and health-related conditions. The article provides detailed descriptions of common irritants, including fleas, lice, mites, and household products, and offers guidance on identifying and managing these issues. It underscores the importance of considering non-insect causes and suggests consulting professionals for persistent problems. Publication date: March 1995.